Effectiveness Of Dismenorhoe Senam In Reducing Dismenorhoe Events In Students In Midwife Study Program In Ubudiyah University Of Indonesia Banda Aceh - Raudhatun Nuzul ZA; Rizky Swastika Renjani (Journal of Midwifery, 2020)
Background: Dysmenorrhea is a physical disorder in women who experience menstrual disorders/stomach cramps. Exercise can increase endorphin production (can increase the body's natural pain), can increase serotonin levels. Gymnastics is one of the relaxation techniques that can be used to reduce pain. In Research Purpose Introduced to Identify Problems of the Dismenorhoe Program in Reducing Dismenorhoe in the Study Program at the Midwifery University, Yogyakarta University, Indonesia. This type of research is a quasi-experimental design with one group pretest-posttest design. The sampling technique is probability sampling, with a sample of 20 respondents, a data collection tool using a Lismore gymnastic observation sheet and a healing scale sheet. Statistical analysis was performed with a Test (T) test. Research results obtained from the analysis of sig. (2-tailed) obtained 0,000 which is significantly very significant or very positive which is higher than α = 0.05. If it is acceptable, it must be accepted, done before and after dysmenorrhoea exercises. It was concluded as the effectiveness of gymnastic dysmenorrhea on the reduction of menstrual pain in a female midwifery study program at the Ubudiyah University of Indonesia. Freed so that the help of gymnastic therapy is used as an alternative intervention to reduce menstrual pain.